A Ledger of Me: Personalizing Healthcare Using Blockchain Technology - Leeming, Gary; Cunningham, James; Ainsworth, John (Frontiers in Medicine, 2019)
Personal Health Records (PHRs) have the potential to give patients fine-grained, personalised and secure access to their own medical data and to enable self-management of care. Emergent trends around the use of Blockchain, or Distributed Ledger Technology, seem to offer solutions to some of the problems faced in enabling these technologies, especially to support issues consent, data exchange and data access. We present an analysis of existing blockchain-based health record solutions and a reference architecture for a “Ledger of Me” system that extends PHR to create a new platform combining the collection and access of medical data and digital interventions with smart contracts. Our intention is to enable patient use of the data in order to support their care and to provide a strong consent mechanisms for sharing of data between different organisations and apps. Ledger of Me is based on around the principle that this combination of event-driven smart contracts, medical record data and patient control is important for the adoption of blockchain-based solutions for the PHR. The reference architecture we present can serve as the basis of a range of future blockchain-based medical application architectures.